2008
DOI: 10.1007/s11010-008-9702-z
|View full text |Cite
|
Sign up to set email alerts
|

Silk sericin protein of tropical tasar silkworm inhibits UVB-induced apoptosis in human skin keratinocytes

Abstract: The silk protein sericin has been identified as a potent antioxidant and photoprotective agent against ultraviolet B (UVB) irradiation in mouse skin model. In this study, we have investigated the anti-apoptotic effect of sericin in UVB (30 mJ/cm2)-irradiated human keratinocytes. Flow cytometry analysis has shown that pre-treatment with sericin inhibits UVB-induced apoptosis. The pre-treatment with sericin suppresses bax expression, up-regulates the expression of bcl-2, prevents both the activation of caspase-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 29 publications
5
96
0
1
Order By: Relevance
“…Seo et al (2011) reported that the cholesterol and blood glucose lowering effect of silk was enhanced by increasing the sericin content. Dash et al (2008) reported that silk sericin from the tasar silkworm inhibits ultraviolet B (UVB)-induced apoptosis in human skin keratinocytes. These findings indicate that silk sericin is an important biomaterial in the cosmetic, functional health food, and biomedical industries.…”
Section: Ftir Measurements and Determination Of The Crystallinity Indexmentioning
confidence: 99%
“…Seo et al (2011) reported that the cholesterol and blood glucose lowering effect of silk was enhanced by increasing the sericin content. Dash et al (2008) reported that silk sericin from the tasar silkworm inhibits ultraviolet B (UVB)-induced apoptosis in human skin keratinocytes. These findings indicate that silk sericin is an important biomaterial in the cosmetic, functional health food, and biomedical industries.…”
Section: Ftir Measurements and Determination Of The Crystallinity Indexmentioning
confidence: 99%
“…Sericin-containing food relives constipation, suppresses development of colon tumors and bowel cancer [2]. Sericin inhibits lipid peroxidation in in vitro rat brain homogenate [3] and inhibits UV-induced apoptosis in human skin keratinocytes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nagai et al (2009) revealed that sericin can promote wound healing. Dash et al (2008) reported that tasar silk sericin inhibits ultraviolet-B-induced apoptosis in human skin keratinocytes.…”
Section: Introductionmentioning
confidence: 99%